3D cone-beam CT of the ankle using a novel twin robotic X-ray system: Assessment of image quality and radiation dose. Issue 119 (October 2019) - Grunz, Jan-Peter; Kunz, Andreas Steven; Gietzen, Carsten Herbert; Weng, Andreas Max; Veyhl-Wichmann, Maike; Ergün, Süleyman; Schmitt, Rainer; Bley, Thorsten Alexander; Gassenmaier, Tobias
Highlights: 3D cone-beam CT is a key feature of the novel twin robotic X-ray system. Standard-dose and low-dose CBCT image quality is suitable for clinical ankle imaging. Significant dose reduction is feasible using the CBCT mode over conventional MSCT. The system looks promising as a one-stop-shop device for ankle imaging in trauma. Abstract: Purpose: To evaluate image quality (IQ) and radiation dose in cone-beam computed tomography (CBCT) of the ankle using a novel twin robotic X-ray system. Method: We examined 16 cadaveric ankles with standard-dose (FD) and low-dose (LD) protocols using the new system's CBCT mode. For comparison, we performed multi-slice CT imaging (MSCT) with a clinical protocol. Three radiologists assessed IQ, noise and artifacts in bone and soft tissue on a five-point Likert scale (1= poor IQ; strong noise or artifacts; 5= excellent IQ; minimal noise or artifacts). Volume CT dose indices (CTDIvol ) were calculated for radiation dose comparison between CBCT and MSCT. Results: Overall IQ was described as very good or excellent by reader 1/2/3 in 62.5/87.5/56.3% of LD, 87.5/87.5/81.3% of FD and 100/87.5/87.5% of MSCT studies. Readers agreed that IQ was better in MSCT than LD (R1/R2/R3; p ≤ 0.008), two also found advantages of MSCT over FD (R1/R3; p ≤ 0.034). Soft tissue noise and artifacts were stronger in FD (all p ≤ 0.002) and LD (all p ≤ 0.001). In bone, artifacts and noise were also more severe in LD (all p < 0.001) and FD (all p ≤ 0.003). CTDIvol for clinical MSCT scans without dose modulation (15.0 ± 0.0 mGy) were higher than for FD (5.3 ± 1.0 mGy) and LD studies (2.9 ± 0.6 mGy; both p < 0.001). Conclusions: Despite MSCT providing better overall IQ than the twin robotic X-ray system's CBCT mode, both cone-beam protocols offer very good IQ in most studies and are suitable for clinical ankle imaging. Standard-dose and especially low-dose CBCT studies deliver up to five times less radiation dose than MSCT imaging.